Pelatihan Peningkatan Kompetensi SDM Pengurus Koperasi Desa Merah Putih Kabupaten Pesisir Selatan - Nora Susanti; Alfattory Rheza Syahrul; Gustia Harini; Mona Amelia; Indra Mulia Pratama; Nilmadesri Rosya; Nisha Selvia; Asti Ananta (Annusfy : Journal of Multidisciplinary Research, 2026)
The Human Resources (HR) Competency Improvement Training for the Management of the Merah Putih Village Cooperative in Pesisir Selatan Regency was conducted as an effort to increase the capacity of the management in professional, transparent, and accountable cooperative management. The implementation methods included lectures, interactive discussions, case studies, and hands-on practice in bookkeeping and analyzing cooperative financial reports. The training results showed an increase in the understanding and skills of cooperative management in recording financial transactions, preparing cooperative financial reports, and analyzing the cooperative's financial condition in a simple manner. In addition, this training encouraged increased awareness of the management of the importance of good cooperative governance. This activity is expected to support the sustainability and performance of the Merah Putih Village Cooperative in Pesisir Selatan Regency and increase member trust in cooperative management